Recombinant Technology in the Development of Materials and Systems for Soft‐Tissue Repair. Issue 16 (14th July 2015) - Girotti, Alessandra; Orbanic, Doriana; Ibáñez‐Fonseca, Arturo; Gonzalez‐Obeso, Constancio; Rodríguez‐Cabello, José Carlos
Abstract : The field of biomedicine is constantly investing significant research efforts in order to gain a more in‐depth understanding of the mechanisms that govern the function of body compartments and to develop creative solutions for the repair and regeneration of damaged tissues. The main overall goal is to develop relatively simple systems that are able to mimic naturally occurring constructs and can therefore be used in regenerative medicine. Recombinant technology, which is widely used to obtain new tailored synthetic genes that express polymeric protein‐based structures, now offers a broad range of advantages for that purpose by permitting the tuning of biological and mechanical properties depending on the intended application while simultaneously ensuring adequate biocompatibility and biodegradability of the scaffold formed by the polymers. This Progress Report is focused on recombinant protein‐based materials that resemble naturally occurring proteins of interest for use in soft tissue repair. An overview of recombinant biomaterials derived from elastin, silk, collagen and resilin is given, along with a description of their characteristics and suggested applications. Current endeavors in this field are continuously providing more‐improved materials in comparison with conventional ones. As such, a great effort is being made to put these materials through clinical trials in order to favor their future use. Abstract : A new family of synthetic protein‐biopolymers, obtained by recombinant biotechnology that provides remarkable properties inherited from natural proteins of provenance, is described. The recombinant biomaterials derived from elastin, silk, collagen, and resilin possess tunable biological and biomechanical characteristics and offer various alternatives that can satisfy and adapt to the specific demands of different soft tissues.